US Dollar swaps after LIBOR - Thomas Heidorn; Rebecca Meier (Frankfurt School of Finance & Management, 2024)
The main focus of this paper is a comprehensive overview of the US reference rate reform, with a particular focus on its implications for USD interest rate swaps (IRS). This paper aims to shed light on the current situation and future developments in a changing financial landscape. This paper discusses the change from US-LIBOR to the Secured Overnight Financing Rate (SOFR) and the Chicago Mercantile Exchange (CME) Term SOFR as new reference rates. Main changes for US IRS against SOFR is a fixing-in-arrears, a loss in the money market term structure, and a change of implicit credit spreads. As only clients are allowed to use CME Term SOFR, banks face basis risk in hedging in the interbank market. As the SOFR is linked to treasuries instead of bank risk, in a crisis the difficulties of banks will increase. Corporate treasuries face a less efficient IRS market, wider ask-bid-spreads, changes in credit spreads, and an increase in complexity as the US money market now differs considerably from the EURO world.
Keywords: 330; LIBOR Reform; LIBOR; Secured Overnight Financing Rate; SOFR; Term SOFR; CME Term SOFR; RFRs; US overnight rate; interest rate swaps; US interest rate swaps; Bank Treasury; Corporate Treasury